A invasão do javali na serra da mantiqueira: aspectos populacionais, uso do habitat e sua relação com o Homem - Gonçalves, Fernando Henrique Puertas (2015)
The Wild Boar (Sus scrofa) is an invasive species, large sized and widely distributed throughout the world, and is currently the largest known mammal distribution. It is considered one of the 100 worst invaders in the world and many ecological and economic damage is attributed to its invasion. Thus, in several World locations management plans are made to control the wild boars populations. For these management strategies take effect, ecological knowledge of the species in the invaded place is required. Therefore, with this work we evaluated the state of the art of the environmental and economic damage caused by the wild boar around the world in places where it is invasive (Chapter 1). In addition, we conducted a populational and ecological study of the wild boar in Serra da Mantiqueira in Minas Gerais, an area considered irreplaceable for the conservation of global biodiversity (Chapter 2). With our study, we concluded that the impact of the boar in its alien range, should be better evaluated, demographic and ecological relationships need to be considered in these studies to the impact be evaluated in a more effectively and accurately way. Still, we found that in Serra da Mantiqueira the boar has a strong relationship with a local temporary resource, the pinion, provided by the pines on the premises and that his relationship with the human being is tenuous. Since while the human activity, such as hunting, can be a limiting factor for its dynamic, agriculture and local breeding may be a factor which would work increasingly the growth and spread of this species in the studied area.